2021
DOI: 10.1111/bjh.17754
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus serological testing in potential allogeneic haematopoietic stem cell transplant recipients: A British Society for Haematology Good Practice Paper

Abstract: The British Society for Haematology (BSH) produces Good-Practice Papers to recommend good practice in areas where there is a limited evidence base but for which a degree of consensus or uniformity is likely to be beneficial to patient care. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) nomenclature was used to evaluate levels of evidence and to assess the strength of recommendations. The GRADE criteria can be found at http:// www.gradeworkinggroup.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It has been suggested that multiple blood product transfusions in hematology patients may lead to false positive CMV serology results, due to the presence of CMV IgG in the transfused products [ 11 , 12 ]. Henceforth, the British Society of Hematology has proposed baseline CMV serology testing for all hematology patients who are likely to proceed to an allogeneic HCT, in order to document their CMV serology status prior to blood product transfusions [ 13 ]. The question on “indeterminate” CMV serology results and potentially falsely-labeled CMV R+ following blood product transfusions has remained open for decades.…”
Section: Cytomegalovirus Immunoglobulin G Titers and Cytomegalovirus ...mentioning
confidence: 99%
“…It has been suggested that multiple blood product transfusions in hematology patients may lead to false positive CMV serology results, due to the presence of CMV IgG in the transfused products [ 11 , 12 ]. Henceforth, the British Society of Hematology has proposed baseline CMV serology testing for all hematology patients who are likely to proceed to an allogeneic HCT, in order to document their CMV serology status prior to blood product transfusions [ 13 ]. The question on “indeterminate” CMV serology results and potentially falsely-labeled CMV R+ following blood product transfusions has remained open for decades.…”
Section: Cytomegalovirus Immunoglobulin G Titers and Cytomegalovirus ...mentioning
confidence: 99%
“…Cytomegalovirus (CMV) serology status of allogeneic hematopoietic cell transplant recipients (allo-HCTRs) is an important variable with potential implications on the selection of a suitable donor but also on administration of primary CMV prophylaxis with letermovir in CMV-positive recipients (CMV R+) [ 1–4 ]. Recent data suggest that almost 1 in 4 allogeneic HCTRs who tested positive for CMV serology may have false-positive results [ 5 , 6 ]. This may, in part, be explained by passive immunity from previous transfusions of blood products [ 5 , 7 ].…”
mentioning
confidence: 99%
“…In the published good practice paper: ‘Cytomegalovirus serological testing in potential allogeneic hematopoietic stem cell transplant recipients’, Morton et al 7 . from the British Society of Haematology (BSH) Guidelines Committee Haematology Oncology Task Force provide recommendations for serological testing in advance of HCT, including the recommendations that CMV serological testing occurs at the time of diagnosis and before blood‐product transfusion, again at subsequent time‐points prior to HCT, and that test results of seronegative patients who convert from seronegative to seropositive be carefully scrutinised.…”
mentioning
confidence: 99%
“…While degree of human leucocyte antigen matching and donor type (related vs. unrelated) are typically prioritised over CMV status, accurate identification of CMV‐seronegative patients is important for donor selection and optimising post‐HCT CMV management strategies. The position paper by Morton et al 7 . highlights the under‐appreciated phenomenon of passive CMV IgG transfer, and advocates for simple practices aimed at early identification of potential future transplant recipients who are CMV seronegative at diagnosis, with critical assessment of an apparent seroconversion before transplantation.…”
mentioning
confidence: 99%
See 1 more Smart Citation